Abdominoplasty in Prune Belly Syndrome. Issue 5 (October 2015) - Dénes, F.T.; Park, R.; Lopes, R.I.; Moscardi, P.R.M.; Srougi, M.
Summary: Introduction: Many patients with Prune Belly Syndrome (PBS) require abdominoplasty alone or in combination with correction of any urogenital abnormalities. This video presents a simplified technique with which to treat the abdominal flaccidity in PBS. Methods: A longitudinal xypho-pubic fusiform figure is drawn on the abdomen, based on the area of skin and subcutaneous tissue to be removed. This is performed with preservation of the musculo-fascial layer and the umbilicus. A lateral elliptical single xypho-pubic line is drawn in the most lax side of the fascia, which is incised along this line. After urinary tract reconstruction and orchidopexy, closure is initiated by suturing the medial edge of the wider fascial flap laterally to the peritoneal side of the contralateral flap. Next, the now outer fascial flap is laid over the inner flap, and a buttonhole is made to expose the umbilicus. The subcutaneous tissue of the inner flap is laterally undermined to gain extra distance for the suture of the outer flap over the inner flap. The subcutaneous tissue and skin are sutured in the midline, incorporating the umbilicus. Results: In a 30-year period, 43 PBS patients underwent this procedure with good cosmetic and long-term functional results. Conclusion: This abdominoplasty technique is simple and presents good functional and cosmetic results in PBS patients.